1996
DOI: 10.1073/pnas.93.22.12433
|View full text |Cite
|
Sign up to set email alerts
|

Human CD8+ T lymphocyte subsets that express HLA class I-specific inhibitory receptors represent oligoclonally or monoclonally expanded cell populations.

Abstract: A small percentage of human T lymphocytes, predominantly CD8+ T cells, express receptors for HLA class I molecules of natural killer type (NK-R) that are inhibitory for T-cell antigen receptor (TCR)-mediated functions. In the present study, it is demonstrated that the various NK-R molecules typically expressed by NK cells are also expressed on periheral blood T lymphocytes. These CD3+ NK-R+ cells have a cell surface phenotype typical of memory cells as indicated by the expression of CD45RO and CD29 and by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

17
185
0
1

Year Published

1998
1998
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 224 publications
(206 citation statements)
references
References 34 publications
17
185
0
1
Order By: Relevance
“…NKRs, which have been orginally described on NK cells, can after binding to MHC class I molecules transduce inhibitory signals for cellular cytotoxicity (40). Concordant with previous findings on CD28 Ϫ T cells, we found that CD8 ϩ CD45RA ϩ CD27 Ϫ T cells express a variety of NKR, both of the C-type lectin and Ig superfamily classes (23,24). In healthy individuals the majority of CD8 ϩ CD27 Ϫ T cells express CD45RA but lack CD28 showing that under physiological conditions CD27 Ϫ and CD28 Ϫ subsets represent largely overlapping populations of CD8 ϩ T cells (7).…”
Section: Discussionsupporting
confidence: 79%
See 2 more Smart Citations
“…NKRs, which have been orginally described on NK cells, can after binding to MHC class I molecules transduce inhibitory signals for cellular cytotoxicity (40). Concordant with previous findings on CD28 Ϫ T cells, we found that CD8 ϩ CD45RA ϩ CD27 Ϫ T cells express a variety of NKR, both of the C-type lectin and Ig superfamily classes (23,24). In healthy individuals the majority of CD8 ϩ CD27 Ϫ T cells express CD45RA but lack CD28 showing that under physiological conditions CD27 Ϫ and CD28 Ϫ subsets represent largely overlapping populations of CD8 ϩ T cells (7).…”
Section: Discussionsupporting
confidence: 79%
“…Furthermore, in search for potential mechanisms that could control the cytotoxic machinery of these cells in vivo, we found normal expression of CD3⑀ and CD3 chains and absence of CTLA-4 expression. However, in agreement with recent finding on CD28 Ϫ T cells (23,24), a strong increase in the expression of various classes of killer-inhibitory receptors was observed when cells maturate into CD8 ϩ CD45RA ϩ CD27 Ϫ effector T cells (25).…”
Section: Cytolytic Mechanisms and Expression Of Activation-regulatingsupporting
confidence: 81%
See 1 more Smart Citation
“…2c). 3c) nor CD94 heterodimers (data not shown) which confirms that CD94 is acquired after antigenic stimulation [28]. (Fig.…”
Section: Introductionsupporting
confidence: 62%
“…KIR-expressing cells of both the CD8 T cell and NK cell lineages have properties consistent with cellular activation. In particular, KIR ϩ CD8 T cells are believed to be a subset of memory T cells (44,45). Furthermore, the ability of KIR ϩ T cells to survive in culture may be enhanced compared with that of KIR Ϫ cells (46).…”
Section: Discussionmentioning
confidence: 99%